THE EFFECT OF THE MASTERY LEARNING MODEL ON THE STUDENTS’ LEARNING OUTCOMES AT CLASS V OF PUBLIC ELEMENTARY SCHOOL 097795 PERASMIAN - Marta S.R Silaban; Patri Janson Silaban; Anton Sitepu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper examines the effect of applying the mastery learning model on students’ learning outcomes on the theme of “Our Friendly Environment” for Class V at SD Negeri 097795 Perasmian in the 2022/2023 academic year. The research employs a quantitative method. The population consisted of 132 students from classes I–VI, and the sample was selected using purposive sampling, totaling 39 students from Class V. The results indicate that students’ learning outcomes using the mastery learning model fall into the excellent category, with an average score of 80.5. The correlation test showed a value of 0.951, which is greater than the r-table value of 0.361 (rcount ≥ rtable), indicating that Ha is accepted. Furthermore, the T-test results show tcount = 2.665 ≥ ttable = 2.048, confirming a significant positive effect of the mastery learning model on students’ learning outcomes. These findings demonstrate that the application of the mastery learning model can significantly improve students’ achievement in learning about the theme of “Our Friendly Environment.”